Help the kelp : a cost-effectiveness analysis of large-scale kelp forest restoration efforts in the Arctic Archipelagos - Eyð Maritudóttir Grønadal 1991- (2023)
Verkefni er lokað til 19.09.2024 Following an increase in green sea urchins (Strongylocentrotus droebachiensis) in the 1970s, vast areas of Northern Norway’s kelp forest ecosystems were transformed into urchin barrens that persist to this day. Kelp forest ecosystems provide various coastal ecosystem services to coastal communities and efforts are being made to restore them. This study aims to find out the most cost-effective restoration methods that can ensure large-scale and sustainable kelp forest restoration, considering various local environmental, biological, and anthropogenic factors. The restoration methods analysed focus on reducing sea urchin densities: ROV, automatic picking, manual picking by volunteers or professionals, and traps. The cost-effectiveness analysis methodology is employed to compare the restoration methods based on their costs, time frames, and effectiveness. Data on each restoration method's expected costs and effectiveness were gathered from local service providers, prior research studies, and expert opinions to facilitate the analysis. The results of the analysis show that methods rooted within the local community can be the most cost-effective restoration method, but these methods are highly dependent on the local community and most likely not suitable for the needed continued scaling up of kelp forest restoration projects. The right restoration method is dependent on scale and site-specific factors and a combination of restoration methods should be considered. The findings of this research will contribute valuable insights for decision-makers and stakeholders involved in kelp forest restoration efforts, aiding in the selection of the most cost-effective and feasible restoration approaches in the Arctic Archipelagos and beyond. Í kjölfar aukningar á grænum ígulkerjum (Strongylocentrotus droebachiensis) á áttunda áratugnum, umbreyttust víðfeðm svæði af þaraskógavistkerfi Norður-Noregs í ígulkerja auðnir sem hafa varað fram á þennan dag. Þaraskógavistkerfi veita ýmsa ...